PENDAMPINGAN PEMERINTAH GAMPONG DALAM PENGELOLAAN ALOKASI DANA GAMPONG (ADG) DI GAMPONG ASAN KECAMATAN LHOKSUKON KABUPATEN ACEH UTARA - Armanda, Dicky; Iskandar; Malahayatie; Jailani, Munawar; Taufiq (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2022)
This community service aims to determine the ability of the Gampong government in Gampong Asan in managing the Village Fund Allocation (ADG). To see the ability of the Gampong government in the management of ADG, the authors refer to management starting from the planning, implementation, reporting and accountability stages. The method used to realize this community service program is material presentation, mentoring, evaluation. The results of community service show that the actual ability of the Gampong Asan government in terms of administrative capabilities has not improved from year to year, but in terms of determining the work program in the use of ADG it is also still minimal. This problem is influenced by several factors, namely; (1) The people of Gampong Asan do not actively participate in all Gampong government affairs, and (2) Supervision by the supervisory team has not been maximized.